Identification of clinically relevant phenotypes in patients with Ebstein anomaly (2018)
Background Ebstein anomaly (EA) is a heterogeneous congenital heart defect (CHD), frequently accompanied by diverse cardiac and extracardiac comorbidities, resulting in a wide range of clinical outcomes. Hypothesis Phenotypic characterization of EA patients has the potential to identify variables that influence prognosis and subgroups with distinct contributing factors. Methods A comprehensive cross‐sectional phenotypic characterization of 147 EA patients from one of the main referral institutions for CHD in Colombia was carried out. The most prevalent comorbidities and distinct subgroups within the patient cohort were identified through cluster analysis. Results The most prevalent cardiac comorbidities identified were atrial septal defect (61%), Wolff‐Parkinson‐White syndrome (WPW; 27%), and right ventricular outflow tract obstruction (25%). Cluster analysis showed that patients can be classified into 2 distinct subgroups with defined phenotypes that determine disease severity and survival. Patients in cluster 1 represented a particularly homogeneous subgroup with a milder spectrum of disease, including only patients with WPW and/or supraventricular tachycardia (SVT). Cluster 2 included patients with more diverse cardiovascular comorbidities. Conclusions This study represents one of the largest phenotypic characterizations of EA patients reported. The data show that EA is a heterogeneous disease, very frequently associated with cardiovascular and noncardiovascular comorbidities. Patients with WPW and SVT represent a homogeneous subgroup that presents with a less severe spectrum of disease and better survival when adequately managed. This should be considered when searching for genetic causes of EA and in the clinical setting.